As tutelas de urgência pleiteadas pelo contribuinte em face da cobrança do crédito tributário - Lucon, Leandro (2023)
This dissertation explores the potential for granting emergency relief and potentially stabilizing summary judgments within the realm of tax law, particularly in tax cases. The objective is to enable taxpayers to counteract the collection of tax credits rapidly and effectively by the Treasury. The study includes an analysis of possible taxpayer defenses in tax foreclosures, as well as proactive actions such as fiscal debt annulment, declaratory of legal-tax relations, consignment of tax credit payments, and writs of mandamus. The primary focus is on the use of emergency relief in these realcase actions, along with potential stabilization of summary judgments. The overarching goal is to either expedite the procedural process or reduce the number of pending demands in the Judiciary